Political Party Pragmatism and the Emergence ofan Empty Column in Gowa’s 2020 Election - Andi Marwah Hermansyah; Nurul Uswatun Hasanah; Anugerah Mulia Utami (Magister Ilmu Pemerintahan FISIP Universitas Mulawaraman, 2025)
The phenomenon of the emergence of an empty column in the 2020 Gowa regional election reveals the practice of political pragmatism that has surfaced in Indonesia's local democracy. Nine out of ten political parties in the Gowa DPRD chose to support the incumbent pair Adnan-Kio, thus creating a single contest against an empty column. This research aims to understand the rationality behind the parties' collective support for a single candidate and examine how this political configuration reflects symptoms of symbolic democracy. Using a narrative qualitative approach, data was obtained through in-depth interviews with political party actors in Gowa, as well as other supporting documentation. The results show that support for a single candidate is based on pragmatic electoral calculations, such as the high electability of Adnan-Kio, concerns about horizontal conflict after the 2015 elections, and the absence of internal cadres who are ready to fight. Instead of carrying out the functions of recruitment and political competition, the parties strengthened the local oligarchy through elite consensus. The existence of an empty column is unable to counterbalance this dominance, making it a procedural symbol of democracy that loses its substance. The conclusion of this study confirms that party political pragmatism in the local context can weaken the quality of electoral democracy and close the space for leadership regeneration. This study recommends party institutional strengthening and nomination threshold reform as an effort to improve the local democratic climate.